2016
DOI: 10.29252/ijn.28.98.58
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s View about the Protection of Privacy by Healthcare Practitioners in Shahid Beheshti Hospital, Qom, Iran

Abstract: ‫ه‬ ‫نیب‬ ‫عببظی‬ ‫حوذ‬ 2 ‫حیذری‬ ‫اکرم‬ 3 ‫صبلحی‬ ‫هحوذ‬ ‫نرگط‬ 4 ‫فیروزی‬ ‫فبطوه‬ 5 ‫شبکری‬ ‫هنصوره‬ 6 ‫قن،‬ ‫پسشکی‬ ‫علوم‬ ‫دانشگبه‬ ‫هبهبیی،‬ ‫و‬ ‫پرظتبری‬ ‫دانشکذه‬ ‫هذیریت،‬ ‫ارشذ‬ ‫کبرشنبض‬ ‫ایراى‬ ‫قن،‬ . 2 ‫ویصه،‬ ‫هراقبت‬ ‫پرظتبری‬ ‫ارشذ‬ ‫کبرشنبض‬ ‫هبهبیی،‬ ‫و‬ ‫پرظتبری‬ ‫دانشکذه‬ ( ‫ایراى‬ ‫قن،‬ ‫قن،‬ ‫پسشکی‬ ‫علوم‬ ‫دانشگبه‬ * ‫هعئول)‬ ‫نویعنذه‬ ‫شوبره‬ ‫توبض:‬ 989937393298 + Email: mabbasinia@modares.ac.ir 3 ‫تخصصی‬ ‫دکترای‬ ‫پسشکی‬ ‫اجتوبعی‬ ، ‫هعنوی‬ ‫ظالهت‬ ‫تحقیقبت‬ ‫هرکس‬ ‫قن،‬ ‫پسشکی‬ ‫علوم… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…24 Getting permission before the examination was reported by only 45.5% of the participants, in Dehghani's study, but 64.7% did not touch if not necessary. 28 On contrary, only 4% of participants in Zirak et al study reported the covering of certain areas of the body when not strictly necessary, 24 and in Adib-Hajbagheri and Zehtabchi study patients stated that exposing of patients' body in presence of the other people not strictly belonging to staff was mentioned by 70.3% of participants. 20 In Aghajani and Dehghan Nayeri's study most of the cases reported providing care by male and female staff for male and female patients, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…24 Getting permission before the examination was reported by only 45.5% of the participants, in Dehghani's study, but 64.7% did not touch if not necessary. 28 On contrary, only 4% of participants in Zirak et al study reported the covering of certain areas of the body when not strictly necessary, 24 and in Adib-Hajbagheri and Zehtabchi study patients stated that exposing of patients' body in presence of the other people not strictly belonging to staff was mentioned by 70.3% of participants. 20 In Aghajani and Dehghan Nayeri's study most of the cases reported providing care by male and female staff for male and female patients, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The scores ranged between 21 and 63, while a higher score indicated more positive attitude. The overall score was divided into three levels of negative (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), moderate (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and positive attitude (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The scoring of the third to seventeenth questions was done inversely.…”
Section: Methodsmentioning
confidence: 99%
“…Nurse-patient gender difference as well as mixed gender wards can endanger the privacy of patients. 45 Dehghani et al 46 reported that patient's privacy was observed at average level, indicating lack of attention to patient's privacy in medical centers. Female patients were more sensitive than males to observance of the physical dimension, avoidance of unnecessary touches, and maintenance of privacy.…”
Section: Duman's Study In Turkey and Walton Et Al's Study On Americanmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies conducted in this area indicated that students are constantly focused on proper procedures and routine responsibilities and are less concerned with dealing with patients' needs and concerns, which are part of the patient safety concept (37). A possible reason is that less clinical education focuses on patient-centered care values and provides inadequate training on person-centered skills (32).…”
mentioning
confidence: 99%